1996
DOI: 10.3354/meps142099
|View full text |Cite
|
Sign up to set email alerts
|

Timing of diapause in relation to the onset of winter in the high-latitude copepods Pseudocalanus acuspes and Acartia longiremis

Abstract: It is proposed that the timing of overwintering diapause in multivoltine, marine copepods is optimised as in insects and limnic copepods. Theoretical models state that resting should begin a period equivalent to 1 generation before the environment becomes unfavourable. Computer simulations and field studies have shown this to apply to insects and limnic copepods. The present paper tests and discusses the model predictions in relation to seasonal environ~nental changes and life history events for populations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Saunders 1971, Watson & Smallman 1971, Hairston & Kearns 1995. It is worth noting that the environmental cues (token stimulus) are different from the ultimate cause of selection (selective environment) (Mayr 1961, Norrbin 1996, Nijhout 2003, and that my model results reflect more on the ultimate cause, although it can help derive possible environmental cues.One of the key assumptions in the present study is that Calanus finmarchicus has a strategy of reducing the risk of catastrophic failure in adverse environmental conditions. Since the diapause for C. finmarchicus occurs at the C5 stage, its risk-reducing strategy is likely to be different from the bet-hedging strategy used by egg-diapausing species who can produce either diapausing or non-diapausing eggs (e.g.…”
mentioning
confidence: 81%
“…Saunders 1971, Watson & Smallman 1971, Hairston & Kearns 1995. It is worth noting that the environmental cues (token stimulus) are different from the ultimate cause of selection (selective environment) (Mayr 1961, Norrbin 1996, Nijhout 2003, and that my model results reflect more on the ultimate cause, although it can help derive possible environmental cues.One of the key assumptions in the present study is that Calanus finmarchicus has a strategy of reducing the risk of catastrophic failure in adverse environmental conditions. Since the diapause for C. finmarchicus occurs at the C5 stage, its risk-reducing strategy is likely to be different from the bet-hedging strategy used by egg-diapausing species who can produce either diapausing or non-diapausing eggs (e.g.…”
mentioning
confidence: 81%
“…was also observed in the White Sea (Pertsova 1981). Norrbin (Norrbin et al 1990;Norrbin 1996) suggested that it is less a continuous process, triggered by the physiological state as proposed by McLaren et al (1989), but rather a speciWc switching date, at which P. acuspes copepodids stop maturation but proceed to accumulate lipids. Klein Breteler and Gonzalez (1988) suspected that changes to poor food conditions are necessary to induce hormonal cessation of development in favor of lipid production.…”
Section: Onset Of Overwinteringmentioning
confidence: 99%
“…Pseudocalanus acuspes mainly inhabits high latitudes (Frost 1989;Runge and Ingram 1991;Siferd and Conover 1992;Norrbin 1996) and due to its absence in the adjacent North Sea (Bucklin et al 2003) and wide distribution in the Arctic, it is most likely a member of the Baltic glacial relict fauna. DiVerent life cycles were described for Pseudocalanus spp.…”
Section: Introductionmentioning
confidence: 99%
“…December through May, (Christiansen 1988)]. Acartia longiremis females undergo dormancy during winter (Davis 1976;Norrbin 1996) while A. bifilosa is adapted to colder temperatures (Schnack 1975) and oversummers as resting eggs (RE) in the North Sea (Chinnery and Williams 2003). Acartia tonsa is originally a tropical species and has been reported in the Baltic since the 1930s (Brylinski 1981 and references therein).…”
Section: Acartia Spp In the Baltic Seamentioning
confidence: 99%